Once poor, always poor? Do initial conditions matter? Evidence from the ECHP - Eirini Andriopoulou; Panos Tsakloglou (Institute for the Study of Labor (IZA), 2011)
The paper analyzes the effects of individual and household characteristics on current poverty status, while controlling for initial conditions, past poverty status and unobserved heterogeneity in 14 European Countries for the period 1994-2000, using the European Community Household Panel. The distinction between true state dependence and individual heterogeneity has very important policy implications, since if the former is the main cause of poverty it is of paramount importance to break the vicious circle of poverty using income-supporting social policies, whereas if it is the latter anti-poverty policies should focus primarily on education, training, development of personal skills and other labour market oriented policies. The empirical results are similar in qualitative but rather different in quantitative terms across EU countries. State dependence remains significant in all specifications, even after controlling for unobserved heterogeneity or when removing possible endogeneity bias.
urn:nbn:de:101:1-201110102188
Keywords: I32; I38; 330; poverty dynamics; EU; ECHP; Armut; Soziale Mobilität; Sozialpolitik; Arbeitsmarktpolitik; EU-Staaten